An observational study comparing two regimens of PGE2 gel for pre-induction cervical ripening at term - Nishat Parveen Begg; Shelley Seth; Aparna Khan Mandal (New Indian Journal of OBGYN)
Objectives: The objective of this study was to compare the outcome in between two groups, one group receiving a 6 hourly repeat regimen (maximum 2 such) and another group receiving a 12 hourly repeat regimen of prostaglandin E 2 gel (maximum 2 such) for pre-induction cervical ripening. Methods: In this observational cross sectional analytical study, pregnant mothers with singleton pregnancy, viable foetus at 37-42 weeks gestational age receiving either repeated doses of prostaglandin E2 gel 0.5 mg every 6 hours or every 12 hours for maximum 2 times were selected matching their baseline characteristics. Mode of delivery and feto-maternal outcome were assessed. The sample size was 114 in each group. Results: More patients are delivering with a single dose of Prostaglandin E2 gel in the 12 hourly repeat group (24.56% in the 6 hourly group versus 30.7% in the 12 hourly group, p value = 0.2998). More patients are delivering vaginally in the 12 hourly repeat group (76.3% in the 6 hourly group versus 82.5% in the 12 hourly group, p = 0.2518). There is lesser number of neonatal and maternal complications with the 12 hourly repeat groups. But none of these results are statistically significant. Conclusion: Repeating prostaglandin E2 gel 12 hourly is as effective as repeating it 6 hourly, rather the 12 hourly regimen has lesser neonatal and maternal complications and is more cost effective although studies on greater population is needed to make these results statistically significant.